Study on the status of liver function abnormalities and its related factors in patients with severe mental disorders in Shanghai community - ZHANG Yixuan; CHEN Chunmei; ZHU Youwei; ZHU Yi; HE Siyuan; LIU Yanli; WANG Na; CAI Jun; XIE Bin; ZHANG Weibo (Shanghai yufang yixue)
ObjectiveTo investigate the status of liver function abnormalities in patients with severe mental disorder (SMD) in Shanghai community, to explore the related factors to abnormal liver function in patients with SMD, and to analyze the effects of the types of mental disorders and medication status on liver function abnormalities.MethodsThe patients with SMD in Jinshan District, Minhang District, Hongkou District and Xuhui District of Shanghai were selected as the research subjects. Questionnaire survey, physical examination and laboratory tests were conducted to obtain their demographic characteristics and liver function indicators such as alanine aminotransferase (ALT) and total bilirubin (TBil). The types of mental disorders and medication status of patients in Jinshan District were also investigated. Abnormalities in liver function were determined by abnormalities in either ALT or TBil. Binary logistic regression analysis was used for multivariate analysis of the status of abnormal liver function, and the effects of mental disorder types and medication status on liver function were analyzed, simultaneously.ResultsA total of 7 251 patients with SMD were finally included into this study, and the rate of liver function abnormality was 22.7%, of which 694 cases (9.6%) had ALT abnormality and 1 084 cases (14.9%) had TBil abnormality. Univariate analysis showed that the rate of liver function abnormalities was higher in males than that in females (χ2=45.026, P<0.001), higher in suburbs than that in urban areas (χ2=25.317, P<0.001), higher in those with higher BMI than in those with lower BMI (χ2=63.748, P<0.001), higher in those with elevated blood pressure (BP) than in those without elevated BP (χ2=24.774, P<0.001), higher in those with elevated blood glucose than in those without elevated blood glucose (χ2=43.345, P<0.001), higher in those with abnormal triglyceride (TG) than in those with normal TG (χ2=15.551, P<0.001), and higher in those with abnormal total cholesterol (TC) than in those with normal TC (χ2=10.962, P=0.001). Multivariate analysis showed that the rate of abnormal liver function was higher in males than that in females (OR=1.53, 95%CI: 1.36‒1.73), higher in suburbs than that in urban areas (OR=1.43, 95%CI: 1.21‒1.70), higher in those with overweight than in those with normal BMI (OR=1.16, 95%CI: 1.01‒1.33), higher in those with obesity than in those with those with normal BMI (OR=1.61, 95%CI: 1.36‒1.91), higher in those with elevated blood glucose than in those without elevated blood glucose (OR=1.39, 95%CI: 1.23‒1.58), and higher in those with abnormal TC than in those with normal TC (OR=1.36, 95%CI: 1.13‒1.65).The difference in the rate of ALT abnormalities among the SMD patients in Jinshan District with different medication status was statistically significant (χ2=21.928, P<0.001). Whereas, the differences in the effects of the types of mental disorders and medication status on the status of liver function abnormalities were not statistically significant(P>0.05).ConclusionThe detection rate of liver function abnormalities in community-based SMD patients in Shanghai is high, and male, suburban, and accompanied by elevated BMI, BP, blood glucose, and TC are risk factors for liver function abnormalities in patients with SMD. Primary healthcare providers should pay more attention to the liver function of patients with SMD and initiate targeted and tailored prevention, detection and treatment measures.